Statina : touch interface engine study on off-plane signal detection - Zhang, Leyu (2012)
Touch interface is the latest innovation of tangible human computer interface. All commercialized technologies nowadays are both expensive and restricted in mobility for big screen applications. “Speech, Touch and Acoustic Tangible Interfaces for Next-generation Applications” (STATINA) aims to break the restrictions for touch technology. Localization estimation is based on calculating the time differences of arrival from tap source to sensors.